Analysis Of Fraud Prevention in Village Fund Management Using Anti-Fraud Awareness and Whistleblowing System - Puspitha, Made Yessi; Astari, Ni Putu Erviani; Artaningrum, Rai Gina (Jurnal Ilmiah Raflesia Akuntansi, 2024)
Fraud is an issue that still affects organizations on a regular basis. The administration of village funds was one of the fraud incidents. Increasing each person's anti-fraud awareness and creating a whistleblowing system that serves as a conduit for reporting any act of violation committed within the organization are two ways to reduce the number of fraud cases involving village fund administration. There were fifteen villages in the Mengwi sub-district that made up the research population. People who might be involved in managing village finances, such as the village consultative council, the village head, the village secretary, and the village treasurer, made up the research samples. Partial Least Square (PLS) analysis with a variance-based SEM equation model was used to evaluate hypotheses. The test results found that anti-fraud awareness had an effect on the whistleblowing system, anti-fraud awareness had an effect on fraud prevention in village fund management, the whistleblowing system had an effect on fraud prevention in village fund management, and anti-fraud awareness through the whistleblowing system had an impact on fraud prevention in village fund management.